Uitbranding in die bediening - A. J. Smuts (Verbum et Ecclesia, 1988)
Ministry burnout Burnout is a hazard to which professional care-givers in the various helping professions are exposed. In this article burnout is described as a multidimensional construct, characterised by a state of emotional overload and subsequent exhaustion, resulting in a state of emotional detachment and depersonalisation. This must be differentiated from related conditions, such as tedium, stress and depression. Burnout as an occupational hazard in the ministry is then discussed. In his daily work the minister is confronted with a situation in which a variety of factors are present which may lead to the state of burnout. The risk increases when a combination of factors leading up to it are present. Interpersonal relations, job setting and personal characteristics all play a part in the development of this problem.